2003
DOI: 10.1207/s15327590ijhc1503_04
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Cursor Orientation and Required Precision on Positioning Movements on Computer Screens

Abstract: Arrowhead cursors used within graphic-user interfaces include implicit directional cues that may not be compatible with desired axis of motion. In addition, arrowhead cursors may not afford the best cues for location, and such effects may be exacerbated when there is a greater need for precise cursor placement. To address the impact of the cursor's orientation on its positioning, 12 participants were required to move cursors (pointing arrows) leftward or rightward to targets (small, medium, or large) on a comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 18 publications
1
26
1
Order By: Relevance
“…Our experimental design differs substantially from the protocol used in the Phillips, Meehan and Triggs study, although our study could be considered to be an extension of their work [22]. Their study focused on determining the presence or absence of S-R compatibility effects with different cursor orientations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our experimental design differs substantially from the protocol used in the Phillips, Meehan and Triggs study, although our study could be considered to be an extension of their work [22]. Their study focused on determining the presence or absence of S-R compatibility effects with different cursor orientations.…”
Section: Discussionmentioning
confidence: 99%
“…Very little work has been done to assess the impact of varying cursor orientations, although an experiment by Phillips, Meehan, and Triggs has directly evaluated the impact of cursor orientation on mouse positioning movements for desktop displays [22]. They found that the directional cues provided by a mouse cursor could induce performance differences.…”
Section: Background and Related Workmentioning
confidence: 99%
“…For example, the cursor might turn into a pointing hand if it is over an hyper-link or into a typewriter cursor if it is inside an editable text area. However, although there are several studies on 2D cursor shapes [20,21], they are only focused on 2D content.…”
Section: Visual Cursorsmentioning
confidence: 99%
“…However, the time-varying characteristics of the cursor trajectory can be revealed by analysing the kinematic variables of the trajectory. The results of such study may provide an understanding of the factors limiting cursor placement (Phillips, Meehan, and Triggs 2003) and indicate what role planning cursor movements, creating terminal guidance, resolving mismatches between display and control coordinate systems, moving cursors across the screen or gauging screen distances (Dillen, Phillips, and Meehan 2005) might play in the problem.…”
Section: Introductionmentioning
confidence: 99%
“…First, the kinematic features of the directional effects were only determined along the main axis of movement (Dillen, Phillips, and Meehan 2005;Donker and Reitsma 2007a;Phillips, Meehan, and Triggs 2003;Meehan 2001, 2005). This dimensional reduction may be valid when the angle of approach is not considered as an individual factor.…”
Section: Introductionmentioning
confidence: 99%